MAKNA SIMBOLIK PROSESI MAKAN BAJAMBA DALAM BARALEK ADAT MINANGKABAU DI DESA BASO KABUPATEN AGAM PROVINSI SUMATERA BARAT - Ade Syaputra; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Makan bajamba procession is one of the traditional culture of Minangkabau society. There are symbolic aspect in makan bajamba procession with special meaning that is represented by clothing, tools used in makan bajamba procession, eating courtesy, figure, to messages in the opening and closing communications (alua) in makan bajamba procession. The purpose of this research was detemining the meaning of symbolic situation, the product of social interaction, and the interpretative of symbolic meaning of makan bajamba procession in custom baralek minangkabau in baso village of distric of agam of west sumatera province. This research used qualitative methode by simbolic interaction approach. Informan of this research is perpetrator makan bajamba , custom figures, and society selected by using purposive technique.. Data collection technique used observation, interview and documentation. The result of research showed that symbolik situation meaning of makan bajamba procession in Baso village consists of physical objects that include clothing and tools used and figures with specific meaning in every part while the social objects from makan bajamba procession consisting of eating courtesy perpetrators makan bajamba, as well as the message content in the opening and closing communications in makan bajamba procession which also has a certain meaning. The meaning of the product of social interaction involves meaning makan bajamba from the side of the actors where makan bajamba is interpreted to have cultural values and the value of togetherness, from the side of custom figures memaknai makan bajamba has cultural values, religion, customs and education, from the side of the Minangkabau society meaning makan bajamba procession has cultural values, education, family values. The meaning of the interpretation of makan bajamba procession includes closed action and open action. Closed actions include internal and external motivations of the perpetrator. as well as feelings of pleasure and pride to be part of the makan bajamba procession. The open act of makan bajamba includes the facial expressions of each actor and the attitudes of the actors who are compact and have an emotional closeness among actors